The Role of Interventional Radiology in Treating Complications following Liver Transplantation. (3rd December 2012) - Mehrzad, Homoyoon; Mangat, Kamarjit
Abstract : Liver transplantation (LT) is used to treat both adult and pediatric patients with end-stage liver disease or acute liver failure. It has become more prevalent as both the surgical technique and postoperative care have improved resulting in a reduced morbidity and mortality. As a result, there are more patients surviving longer after liver transplantation. Despite this, there remain serious complications from the procedure that have a significant outcome on the patient and may result in retransplantation. At the same time, there have been significant advances in the field of interventional radiology both in terms of technology and how these apply to the patients. In this paper, we review the commonest complications, diagnostic tests, and interventional management options available.